The Effect of Preoperative Antiplatelet Therapy on Early Postoperative Rehemorrhage and Outcomes in Patients With Spontaneous Intracranial Hematoma - Yang, Junhua; Liu, Qingyuan; Mo, Shaohua; Wang, Kaiwen; Li, Maogui; Wu, Jun; Jiang, Pengjun; Yang, Shuzhe; Guo, Rui; Yang, Yi; Zhang, Jiaming; Liu, Yang; et al. (Frontiers in Aging Neuroscience, 2021)
Abstract Background and purpose The effect of antiplatelet therapy (APT) on early postoperative rehemorrhage and outcomes of patients with spontaneous intracerebral hemorrhage (ICH) is still unclear. This study is to evaluate the effect of preoperative APT on early postoperative rehemorrhage and outcomes in ICH patients. Methods This was a multicenter cohort study. ICH patients undergoing surgery were divided into APT group and nAPT group according to whether patients received APT or not. Chi-square test, t and Mann-Whitney U test were used to compared the differences in variables, postoperative rehematoma and outcomes between groups. Multivariate logistics regression analysis was used to correct for confounding variables which were different in groups comparison. Results 150 ICH patients undergoing surgical treatment were consecutively included in this study. 35 (23.33%) people were included in APT group, while 115 (76.67%) people were included in nAPT group. The incidence of early postoperative rehemorrhage in APT group was significantly higher than that in nAPT group (25.7% VS 10.4%, p=0.047＜0.05). After adjustment for age, ischemic stroke history and ventricular hematoma, preoperative APT had no significant effect on early postoperative rehemorrhage (p= 0.067). There was no statistical difference between two groups in early poorer outcomes (p=0.222) at 14 days after surgery. After adjustment for age, ischemic stroke history and ventricular hematoma, preoperative APT also had no significant effect on early poorer mRS (p=0.072). Conclusions In conclusion, preoperative APT appears to be safe and have no significant effect on early postoperative rehematoma and outcomes in ICH patients.